A COOPERATIVE EDUCATION PROGRAM IN PUBLIC ACCOUNTING. - Burnet, Mary E.; Travis, Arden L. (The Accounting Review, 1964)
The article focuses on a cooperative education program in public accounting in the U.S. Public accounting majors in the School of Business Administration of the Rochester Institute of Technology are getting practical experience as well as academic training for the career of their choice. The institute has pioneered in many fields and its cooperative or work-study program began in 1912, just six years after the cooperative plan of education was originated at the University of Cincinnati. In order to improve the program both from the standpoint of employers and students, a new arrangement went into effect in the fall of 1962. Under it, students attend classes for three consecutive quarters during their freshman and sophomore years. In their junior year, students will work two quarters and be in school two quarters, while as seniors; students will work two quarters and be in school three quarters. The public accounting program at the Rochester Institute of Technology has been registered by the State Education Department of the State of New York as an approved program, and therefore, students graduating as public accounting majors have completed the educational requirements for taking the Certified Public Accountants examination in the State of New York.